Exploring the importance of a sense of belonging for a sense of ownership in learning - du Toit-Brits, C. (South African Journal of Higher Education, 2022)
In construction and supporting learners’ sense of belonging in a learning environment, teachers have proposed stimulating learners’ desire to learn. This article will present the results of a literature review on belonging to support the authors’ viewpoint that it is needed to foster a sense of belonging and accentuate school belonging in learning programs, practices, and research. This article explores how a sense of belonging prepares and support learners to take ownership of learning to promote self-directed learning (SDL) in learning communities. It argues for the need to locate the need for belonging in learning communities and define the essence of success for taking ownership of learning. Furthermore, the article will show how a sense of belonging is an essential human necessity and that nurturing a sense of belonging can be seen as imperative, irrespective of learners who do not have a deep understanding of non-belonging. However, for learners to effectively be part of a learning community, a nuanced approach to belonging should be followed to provide learners with a sense of belongingness for taking ownership of learning and how to support learners who do not feel like they belong (fit in) or feel left out. Nevertheless, this article will also attempt to show that, although there might be learners who experience deep senses of non-belonging, they learn, but they manage to excel, it still remains essential to fulfil the need to belong in educational contexts. In terms of the latter, this article proposes that belonging is one of the first things teachers ought to attend because when learners do not feel like they belong, they can find it challenging to have a sense of ownership. Hence, the article aims (a) to review the theoretical literature on a sense of belonging, emphasising its essential features. Then, in light of the essential features recognised, the author proposes (b) general and practical recommendations for educational stakeholders wanting to build and support learners’ sense of belonging at school as well as towards how teachers can cultivate a sense of belonging in learning communities to support learners who do not feel like they belong (fit in) or feel left out.